Chemical Constituents and Antileishmanial and Antibacterial Activities of Essential Oils from Scheelea phalerata - Oliveira, Daiane M.; Furtado, Fabiana B. [UNESP]; Gomes, Antoniel A. S. [UNESP]; Belut, Belisa R.; Nascimento, Evandro A.; Morais, Sérgio A. L.; Martins, Carlos H. G.; Santos, Vinícius C. O.; Da Silva, Claudio V.; Teixeira, Thaise L.; Cunha, Luís C. S.; Oliveira, Alberto De; et al. (American Chemical Society (ACS), 2020)
Scheelea phalerata Mart. ex Spreng (Arecaceae) is a palm tree found in the Brazilian cerrado. There are no topics related to volatile oils from S. phalerata leaves in the literature. This work determines its chemical composition and evaluates the biological activity under two different seasonal conditions (dry and rainy seasons). The dry essential oil yield was 0.034 ± 0.001% and the rainy essential oil yield was 0.011 ± 0.003%. Both essential oils presented different qualitative and quantitative compositions (99.4 and 98.5%). The main constituents of the dry essential oil were phytol (36.7%), nonadecane (9.7%), linolenic acid (9.1%), (Z)-hex-3-en-1-ol (4.2%), and squalene (4.0%). The main constituents of the rainy essential oil were phytol (26.1%), palmitic acid (18.7%), hexan-1-ol (15.6%), (Z)-hex-3-en-1-ol (9.7%), and oleic acid (4.0%). The antileishmanial activity against promastigotes of Leishmania amazonensis was observed only for the rainy season essential oil (IC50 value of 165.05 ± 33.26 μg mL-1). A molecular docking study showed that alcohols exert a paramount efficacy and that the action of some essential oil compounds may be similar to that of amphotericin B. Still, only the essential oil from the dry season showed moderate antibacterial activity against S. sanguinis (MICs 200-400 μg mL-1). The cytotoxicity against Vero cells was identical (>512) for both essential oils. The novel data here for both chemical characterization and biological activity, in particular, evidence that the action of these compounds is similar to that of amphotericin B, provide valuable information to the drug-discovery field.